Long-term effects of weather-induced migration on urban labor and housing markets - Matias Busso; Juan Pablo Chauvin (Inter-American Development Bank (IDB), 2023)
This paper explores the effects of weather-induced rural-urban migration on urban labor and housing markets in Brazil. In order to identify causal effects, it uses weather shocks to the rural municipalities of origin of migrants. We show that larger migration shocks led to an increase in employment growth and a reduction in wage growth of 4 and 5 percent, respectively. The increased migration flows also affected the housing market in destination cities. On average, it led to 1 percent faster growth of the housing stock, accompanied by 5 percent faster growth in housing rents. These effects vary sharply by housing quality. We find a substantial positive effect on the growth rates of the most precarious housing units (with no effect on rents) and a negative effect on the growth of higher-quality housing units (with a positive effect on rents). This suggests that rural immigration growth slowed down housing-quality upgrading in destination cities.
Keywords: J46; J61; O18; R23; 330; Weather-induced migration; Rural-urban migration; Urban labor markets; Urban housing markets; Developing countries